PENINGKATAN KEMAMPUAN KOSA KATA MELALUI KEGIATAN BERMAIN PERAN PADA ANAK USIA DINI - Miftahul Jannah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
The problem in this study is that children's vocabulary skills are still difficult to speak. This study aims to determine the increase in vocabulary skills through role playing activities in group A children at Al-Amin Kindergarten, Palopo City. The type of research used is classroom action research. Data collection techniques through observation, interviews, and documentation. The data analysis technique used is descriptive qualitative and quantitative analysis techniques. The results showed that role playing activities can improve children's vocabulary skills. The improvement can be seen in the research results. In the initial condition, there were five children (50%) in the BB category, three children (30%) in the MB category, two children (20%) in the BSH category. After taking action in cycle I the results in children's vocabulary skills through role playing activities have increased, namely there is one child (10%) in the BB category, there are two children (20%) in the MB category, five children (50%) in the BSH category and two children (20%) in the BSB category. In the second cycle, there were no children in the BB and MB categories, seven children (70%) in the BSH category and three children (30%) in the BSB category. This research was stopped until the second cycle because the criteria for success indicators had been achieved.